1995
DOI: 10.1097/00000542-199501000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Inhibits Glutamate-, N-Methyl-D-Aspartate-, and Quisqualate-stimulated cGMP Production in Cultured Cerebral Neurons 

Abstract: The authors' data demonstrate that ketamine inhibited NO synthesis stimulated by NMDA- and non-NMDA-receptor specific analogs. Our findings indicate that blockade of QUIS- as well as NMDA-subtypes of GLU- receptor may be important in the development of ketamine-induced anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(14 citation statements)
references
References 61 publications
0
12
0
2
Order By: Relevance
“…Exposure of cultured hippocampal neurons to ketamine induced HDAC5 phosphorylation in a concentration-dependent manner, which reached peak levels at ∼100 nM (Fig. 1A), a concentration lower than comparable plasma concentrations required to produce anesthesia in humans (5-10 μM) (15). The response to ketamine displayed an inverted U, as higher doses had no effect on HDAC5 phosphorylation.…”
Section: Resultsmentioning
confidence: 93%
“…Exposure of cultured hippocampal neurons to ketamine induced HDAC5 phosphorylation in a concentration-dependent manner, which reached peak levels at ∼100 nM (Fig. 1A), a concentration lower than comparable plasma concentrations required to produce anesthesia in humans (5-10 μM) (15). The response to ketamine displayed an inverted U, as higher doses had no effect on HDAC5 phosphorylation.…”
Section: Resultsmentioning
confidence: 93%
“…Thus, the effect of ketamine is considered to be synergic with that of intrathecal bupivacaine because combined administration demonstrates better blocking with a longer duration (13,29). Several in vitro and in vivo studies have demonstrated the potential of ketamine for producing neuroprotective effects (43)(44)(45). This ability is indicated by the observations that ketamine blocks NMDA-receptor activation, mediates beneficial changes in apoptosis-regulating proteins and interferes with the inflammatory response to injury when administered in typical sedative or anesthetic doses.…”
Section: Discussionmentioning
confidence: 99%
“…This analogue probably acts through a mechanism different from L-glutamate (Gonzales et al, 1995), as the inhibitory effect of kainate, but not L-glutamate, could be abolished by the non-NMDA receptor antagonist CNQX (Watkins et al, 1990). These results suggest that the inhibitory effect of kainate on the EFS vas deferens contraction is mediated by non-NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%